Nunal sa tubig - Bernal, Ishmael; Arago, Jorge; Oropesa, Elizabeth; Ramirez, Daria; Estregan, George; Luansing, Ella.; Rustia, Ruben; Rustica Carpio; Leticia De Guzman; Crown Seven Production ([Manila s.n., 1976)
It tells the story of Benjamin, Maria and Chedeng who lived on an island in Laguna de Bay where fishing is the main source of livelihood and how they are affected by progress. The sea is slowly being polluted by the growth of industries on the nearby towns.
Subtitle: English.
Jorge Arago, writer
Elizabeth Oropesa, Daria Ramirez, George Estregan, Ella Luansing, Ruben Rustia, Rustica Carpio, Leticia De Guzman
Keywords: Fishing -- Philippines -- Drama; Urbanization -- Philippines -- Drama; Motion pictures -- Philippines